Farmer perceptions of bird damage and control in arable crops - Coleman, J.; Spurr, E.B. (New Zealand Plant Protection, 2001)
One hundred arable farmers from across New Zealand were randomly selected and interviewed in summer 2000 to assess their perceptions of the nature and extent of bird damage to their crops the bird species involved the factors affecting the level of damage and the type and cost of any bird control undertaken Most farmers considered birds caused serious damage to their crops with wheat barley peas and some speciality seed crops such as brassicas borage and evening primrose most at risk Damage was rarely perceived to exceed 5 in cereals but was often higher in speciality crops It was most severe at seed maturation The birds responsible for most of the damage were house sparrows and greenfinches Most farmers undertook some form of bird control to protect their crops with shooting gas guns and avicides most commonly used The overall expenditure on bird control was far less than the value of the damage reported